2016
DOI: 10.2147/ott.s100905
|View full text |Cite
|
Sign up to set email alerts
|

ABCB1 and ABCC2 and the risk of distant metastasis in Thai breast cancer patients treated with tamoxifen

Abstract: BackgroundGenetic polymorphisms of drug-metabolizing enzymes and transporters have been extensively studied with regard to tamoxifen treatment outcomes. However, the results are inconclusive. Analysis of organ-specific metastasis may reveal the association of these pharmacogenetic factors. The aim of this study is to investigate the impact of CYP3A5, CYP2D6, ABCB1, and ABCC2 polymorphisms on the risk of all distant and organ-specific metastases in Thai patients who received tamoxifen adjuvant therapy.MethodsGe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 41 publications
0
4
0
1
Order By: Relevance
“…Two ABC transporters, ABCC2 and ABCB1, exhibited the most significant differences (fold change = 2.73, p = 0.0006 and fold change = 2.58, p = 0.0003, respectively). These proteins are involved in the transport of tamoxifen ( Iusuf et al., 2011 ), and polymorphisms in their genes are associated with the risk of metastasis and recurrence in hormone receptor-positive breast cancer ( Kiyotani et al., 2010 ; Sensorn et al., 2013 , 2016 ), suggesting their roles in the metastasis process. Furthermore, overexpression of these genes confers cancer cell resistance to various chemotherapeutic agents ( Taniguchi et al., 1996 ; Xie et al., 2010 ).…”
Section: Resultsmentioning
confidence: 99%
“…Two ABC transporters, ABCC2 and ABCB1, exhibited the most significant differences (fold change = 2.73, p = 0.0006 and fold change = 2.58, p = 0.0003, respectively). These proteins are involved in the transport of tamoxifen ( Iusuf et al., 2011 ), and polymorphisms in their genes are associated with the risk of metastasis and recurrence in hormone receptor-positive breast cancer ( Kiyotani et al., 2010 ; Sensorn et al., 2013 , 2016 ), suggesting their roles in the metastasis process. Furthermore, overexpression of these genes confers cancer cell resistance to various chemotherapeutic agents ( Taniguchi et al., 1996 ; Xie et al., 2010 ).…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, several other studies also substantiated the impact of ABCB1 in relation to clinical outcome of tamoxifen. ABCB1 polymorphism was associated with risk of recurrence or disease free survival (DFS), in breast cancer patients on tamoxifen treatment [16,42,43].…”
Section: Discussionmentioning
confidence: 99%
“…Another study of 73 breast cancer patients also found reduced tamoxifen efficacy associated with a wild-type allele ABCC2 as compared to variant alleles with reduced ABCC2 activity [ 41 ]. Further, they found that the combination of higher ABCC2 activity (ABCC2 CC) with higher ABCB1 activity (ABCB1 CT + TT) was associated with reduced disease-free survival compared to any other combination of genotypes for ABCC2 and ABCB1.…”
Section: Inducers Of Enzymes/transporters and Tamoxifen Efficacymentioning
confidence: 99%